2006
DOI: 10.1097/01.ajp.0000177509.93523.68
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Quality of Life in Adolescents With Chronic Pain

Abstract: In addition to pain, psychosocial factors (vulnerability, reinforcement, modeling, and coping) are strongly associated with quality of life in adolescents with chronic pain. These results may contribute to psychological interventions focused on psychological adaptation in young pain patients to improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…In further support, several studies found maladaptive influences of parental protective responses to child pain [10,37,43,54,55], which seem especially prevalent in parents who catastrophize about child pain [5,48].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In further support, several studies found maladaptive influences of parental protective responses to child pain [10,37,43,54,55], which seem especially prevalent in parents who catastrophize about child pain [5,48].…”
Section: Discussionmentioning
confidence: 85%
“…Parental responses may vary from ignoring and discouraging to protecting and comforting [4,9,32]. Although the efficacy of any particular parental strategy should be understood in its particular context, a general finding has emerged that parental attention to pain, typically operationalized as solicitousness, overprotectiveness, or reassurance, has a negative effect on child coping [10,37,43,54,55]. In contrast, parental behavior that encourages coping by directing children to distract or introducing new strategies is related to less child distress and pain [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…The associated functional disability that many chronic pain sufferers experience results in decreased quality of life in many areas, including participation in physical activities, emotional well-being, and school functioning. 13, 27,35 Many studies of adult chronic pain and associated disability focus on workplace functioning. School is the "work" of childhood and adolescence, but little is known about how pain affects adolescents' school success.…”
mentioning
confidence: 99%
“…8,43 Elevated school absences have been documented in youth with chronic pain. 4,8,27,30,31,43 In a clinical population, Konijnenberg et al 19 found that 51% of participants reported currently missing at least 1 to 3 days of school per month. Still more striking, 14% of the sample attended no school for 3 months or longer.…”
mentioning
confidence: 99%
“…After initial fulfillment of dependency needs, attention is gradually withdrawn from the pain. Emotion-focused avoidance coping strategies decrease the relation between pain intensity and psychological functioning [32]. The soldiers are encouraged to communicate anxiety and fears and explore psychosocial stressors while actively participating in choices and managing issues that are out of their control.…”
Section: The Walter Reed Army Medical Center Experiencementioning
confidence: 99%